Corporatisation of universities deepens inequalities by ignoring social injustices and restricting access to higher education - Dlamini, R. (South African Journal of Higher Education, 2019)
There has been an unprecedented demand for equitable access to post-secondary education post 1994, perhaps because of the change in policies broadening participation of black people in traditional institutions of higher learning in South Africa. The dramatic increase of people of colour attending institutions of higher learning coincided with shrinking government subsidies, which led to universities redesigning their identity according to corporate culture. Thus, they turned to double digit fee increases and persistent long-term outsourcing of services to overcome the problem of funding insecurities. However, it is not clear how corporatization of institutions of higher education enables equitable access and efficient delivery of higher education to the majority of blacks who were previously disadvantaged by apartheid policies. The primary objective of this paper is to conduct a meta-synthesis of a systematically retrieved sample of empirical academic literature to present an argument on the systemic deficits in corporatization of higher education and the corporate identity which distort the ideal university. The PRISMA statement is followed to ensure transparent and complete synthesis of the literature reviewed to maintain the integrity of individual studies. Thereafter, the paper presents a detailed account of how corporatization of universities deepens inequalities; ignores social injustices and restricts access to higher education. In addition, the paper makes a claim that corporatization of universities impairs the academic quality and freedom of the university as well as portrays education as ‘private good’ for self-actualization.